Handbook of natural language processing - Indurkhya, Nitin; Damerau, Frederick J. (Frederick Jacob), 1931- (Chapman & Hall/CRC machine learning & pattern recognition series., 2010)
Provides a comprehensive, modern reference of practical tools and techniques for implementing natural language processing in computer systems. This title covers classical methods, empirical and statistical techniques, and various applications. It describes how the techniques can be applied to European and Asian languages as well as English.